LEGAL ASPECTS OF PATIENTS IN RESTRAINT, SECLUSION AND CONFINEMENT: A THEMATIC ANALYSIS - Malfasari, Eka; Keliat, Budi Anna; Daulima, Novy Helena Chatarina; Wardani, Ice Yulia; Subu, Muhammad Arsyad (Jurnal Persatuan Perawat Nasional Indonesia (JPPNI), 2024)
Patient violence poses a real risk to themselves, others and environment. Violent behaviors can be controlled through restraint and seclusion at mental hospital and confinement at community. There are no specific policies and legal aspects concerning restraint, seclusion and confinement in Indonesia.  Purpose of this study: This study aimed to analyze policies and legal aspects concerning restraint, seclusion and confinement in Indonesia and foreign countries. Method: It was a qualitative study using thematic analysis that analyzed 8 foreign documents and 7 Indonesian documents. It analyzed the similarities and differences of legal aspects concerning restraint, seclusion and confinement based on the documents. Results: Themes from foreign countries were (1) restraint, seclusion and confinement as the last intervention; (2) family empowerment;(3) humanizing patients with restraint, seclusion and confinement; (4) safety and comfort of restraint, seclusion and confinement intervention for patients; (5) safety and comfort of restraint, seclusion and confinement intervention for nurses. Themes from Indonesia were (1) safety and comfort of restraint, seclusion and confinement intervention for patients and nurses; (2) protection against human. Discussion:Indonesia must have specific regulation about restraint, seclusion and confinement for mental disorder. Conclusion: This study provides an overview of the policies implemented in Indonesia. Keywords: Legal Aspect; Confinement; Policies; Restraint; Seclusion